OSTEOSSARCOMA: DEFINIÇÃO, INCIDÊNCIA E TRATAMENTOS DA DOENÇA - Gregolon, Bruna; Antunes, Rafaela; Bernardo, Ana Maressa; Schneider, Taiane; Cezario, Kamila Cerbaro; Fraporti, Liziara (Anais de Saúde Coletiva, 2023)
Sarcoma Osteogênico. Osteossarcoma. Antineoplásicos.